Development, characterization, and antioxidant evaluation of corn starch‐based composite films containing tea polyphenols. Issue 15 (17th November 2021) - Yu, Xietian; Lin, Li; Mei, Liping; Sun, Chengyi; Zhu, Zhijie; Du, Xianfeng; Chen, Peirong
Abstract: Corn starch/polyvinyl alcohol (PVA) composite films containing different concentrations of tea polyphenols (TP) were fabricated by casting. Scanning electron microscopy and atomic force microscopy images showed that when the TP content was less than 8%, the films were relatively uniform, but with increasing TP concentration, the films became rougher and uneven. Fourier transform infrared, 13 C nuclear magnetic resonance, and X‐ray diffraction techniques were used to investigate the interactions between TP, starch, and PVA. The incorporation of TP deepened the color and increased the opacity and solubility of the films. The tensile strength and elongation at break first increased and then decreased with increasing TP content. Furthermore, the addition of TP increased the antioxidant activity of the films, specifically, their ability to scavenge 2, 2‐diphenyl‐1‐picrylhydrazyl and 2, 2′‐azinobis (3‐ethylberizothiazoline‐6‐sulfonic acid). The addition of TP can effectively enhance the performance of starch composite films and their potential for application in antioxidant food packaging. Abstract : In this study, tea polyphenols (TP) are incorporated into starch/PVA matrix to develop biodegradable composite films with high antioxidant activities. The interactions and compatibility of starch with PVA and TP with film‐forming substrate are studied. The addition of TP improved the ultraviolet light barrier, solubility, tensile strength and antioxidant activity of the composite film.